Leaving group ability in nucleophilic aromatic amination by sodium hydride-lithium iodide composite - Pang, Jia Hao (2022)
The methoxy group is generally considered as a poor leaving group for nucleophilic substitution reactions. This work verified the superior ability of the methoxy group in nucleophilic amination of arenes mediated by the sodium hydride and lithium iodide through experimental and computational approaches.